A feasibility study on the establishment of a Barangay Reading Center in Concepcion Dos Marikina City in compliance with RA 7743 - Adriano, Nikolai V. (2012)
Republic Act 7743 is an act providing for the establishment of congressional, city and municipal libraries and barangay reading centers throughout the Philippines. However the provisions of the law are not fully implemented up to the barangay level thus very few barangay reading centers exist in the whole Philippines. This is the primary reason why the study concerned on the feasibility to establish a barangay reading center in Concepcion Dos Marikina City.